eCM 2009
DOI: 10.22203/ecm.v018a06
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of nano-fibrous PCL-b-PLLA scaffolds for cartilage tissue engineering

Abstract: Nano-fibrous scaffolds which could potentially mimic the architecture of extracellular matrix (ECM) have been considered a good candidate matrix for cell delivery in tissue engineering applications. In the present study, a semicrystalline diblock copolymer, poly(ε-caprolactone)-block-poly(L-lactide) (PCL-b-PLLA), was synthesized and utilized to fabricate nano-fibrous scaffolds via a thermally induced phase separation process. Uniform nano-fibrous networks were created by quenching a PCL-b-PLLA/THF homogenous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…There are various applications of spermatogonial stem cell transplantation beyond basic research [38]. For instance, cancer treatment can cause infertility; thus, obtaining and storing of spermatogonial stem cells from patients could be a promising way to restore and preserve fertility [38][39][40]. Also in testicular torsion, testicular biopsy is likely to provide the spermatogonial stem cells for cryopreservation, storage, and transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…There are various applications of spermatogonial stem cell transplantation beyond basic research [38]. For instance, cancer treatment can cause infertility; thus, obtaining and storing of spermatogonial stem cells from patients could be a promising way to restore and preserve fertility [38][39][40]. Also in testicular torsion, testicular biopsy is likely to provide the spermatogonial stem cells for cryopreservation, storage, and transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…2), there was a high degree of inter-connectivity between pores and smooth transitions between layers of different porosities, properties that can be easily controlled by the size and quantity of the porogen (e.g., salt crystal in this study; ref. 20). We show the influence of pore size on bridging and penetration by two representative cell types found in tubular or hollow tissues, epithelial, and smooth muscle cells (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the co-polymer systems can self-organize into different complex structures. He et al reported that, with a similar fiber diameter, nano-fibrous structures were obtained at a relative higher T gels in the pure PLLA system than in the PCL-b-PLLA system (39). Polymer crystallization behavior plays an important role in nanofiber formation.…”
Section: Effect Of Polymer Propertiesmentioning
confidence: 98%
“…During the gelation process, the gelation temperature (T gel ) exerts critical influence to the architecture of the resultant scaffolds (38,39). Although all the scaffolds were nanofibrous networks, only the structures of the scaffolds produced at lower temperatures (−40°C and −20°C) were uniform.…”
Section: Effect Of Gelation Temperaturementioning
confidence: 99%